Social Communication as a Means of Increasing Community Involvement in Education in Aceh - Zulfikar Arahman; Muslem Hamdani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Social communication plays a crucial role in increasing community engagement in education, especially in regions with strong cultural characteristics like Aceh. However, limited access to information and low digital literacy pose challenges in optimizing the role of social communication in education. This study aims to identify effective social communication strategies to enhance community involvement in education in Aceh. The research employs field research methods, using data collection techniques such as in-depth interviews, participatory observation, and document analysis of education policies. The findings indicate that community-based and local wisdom-driven social communication is more effective in fostering awareness and participation than modern communication media. Key factors influencing the effectiveness of social communication include the role of religious leaders, social organizations, and community-based discussion methods. Furthermore, the study reveals persistent challenges in utilizing digital communication technologies to support community participation in education. Therefore, adaptive policies that integrate community-based communication and digital technology are needed to expand access to educational information. The primary contribution of this research is to provide insights into how social communication can be optimized as a strategy to enhance community involvement in education while offering recommendations for education policies grounded in local wisdom.